Enhancing the Performance of Paroxetine Hydrochloride Mucoadhesive Buccal Tablets for Anti-depression Treatment: A Response Surface Methodological Approach (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: This study aimed to find a way to make buccal tablets of Paroxetine Hydrochloride (PRX) that stickto mucous membranes effectively and have a controlled release. Materials and Methods: Response surfaceapproach, notably a three-level strategy, and Design Expert® software were used to develop and optimizeParoxetine Hydrochloride buccal tablets for oral medication delivery. PRX’s unidirectional mucoadhesivebuccal tablets were prepared by direct compression using Carbopol 934P and HPMC K15M as mucoadhesivecontrolled release agents. The developed formulations were assessed for a variety of characteristics before andafter compression, as well as for surface pH, swelling, ex vivo mucoadhesive strength, and in vitro and ex vivodrug release. Results: The Fourier-transformed infrared spectrum and differential scanning calorimetry peakof Paroxetine Hydrochloride indicated that there was no interaction between the drug and the used excipients.Swelling index research found that polymer concentration is directly correlated with swelling. Formulation F4Paroxetine Hydrochloride exhibited the highest mucoadhesive strength (0.93 ± 0.06N) with the highest ratioof carbopol 934P and HPMC K15M (2:5), while formulation F11 had the weakest force (0.68 ± 0.04N) due tohigher and lower polymer quantities. In in vitro release trials, tablet formulation F9 demonstrated superior releasecharacteristics (95.57 ± 0.42%, 8 h) compared to other formulations due to carbopol 934P and HPMC K15Mswelling, drug release was slow (0–63.34%) for the first 4 h. Drug release increased from 4 to 8 h, reaching95.57 ± 0.42% by the end. Ex vivo permeation research using drug release experiments identified formulationF9 as the best, with a 70.88 ± 2.65% drug release compared to 42.65 ± 2.52%. Conclusion: The ideal controlledrelease system would release the medication at the right time and keep it at the therapeutic level for as long aspossible. According to dissolving profiles and swelling data, mucoadhesive buccal tablets released ParoxetineHydrochloride mostly due to the quickly hydrating polymer. This study aimed to bypass first-pass metabolism andincrease Paroxetine Hydrochloride bioavailability.